DOES EVERSHARING PROBLEMS WILL TRIGGER AFFECTIVE DISORDER TO THE EMPATHIZER? - Mohd Khairi, Nur Khalida Nia Binti (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction – Social networking sites (SNSs) have become an inescapable part of present day culture, which may moreover influence the mental well-being of the clients. Affective disorders clutters to the same degree of discouragement and uneasiness seems to have occurred to show biface intuitive with the interpersonal atmosphere that impact the way of sickness commencement as well as preservation. The relationship between oversharing syndromes exists as to affiliations that SNSs utilize may have with disposition emotional clutter to the empaths. Social isolation, anxiety, low self-esteem, and self-disclosure lead to the development and exacerbation of depression and other psychiatric disorders primarily with the targeted populations and individuals with pre-existing psychiatric disorders. Management of stress, anxiety, and burnout syndromes amongst the SNSs users is imperative to build a healthy environment and safe mental state in the future. Methods – Author used 19 journals that discussed the relationship of risk factors of low mood and mental distress of empathy. Results – Depressioni and anxietyi may have a role in influencing the sizei and structurei of a person's socialinetwork, the contacts' worth within those networks, and howi well or reasonable to implement use of relational integration or expanded to offer social support. Discuss – Affective empathy, on the one hand, is understood to refer to the perception of an affective state that is similar to that of the observed individual, encompassing phenomena like emotional contagion and affective resonance. Conclusion – According to SNSs point of view, there is a devising association interpolated poor temperament and empathici suffering albeit observing significant's pain. This could have significant ramifications for persons suffering from negative mood is indeed one of the causative factors. Most common symptoms and increased personal anguish from witnessing others' suffering can lead to avoidance and social disengagement. More focused and controlled study on the mental health effects of empathy and social media should be done ahead of time. This is in order to have a better knowledge of the effects of the oversharing syndrome and, as a result, to create a mental SNSs environment that is beneficial for all users.